WAYS OF ORGANIZING KNOWLEDGE CONTROL IN DISTANCE EDUCATION SYSTEMS - Romanenko, I. A.; Stolbov, V. F.; Kalachova, V. V. (Radio Electronics, Computer Science, Control, 2024)
The article researches the problems of improving the teaching efficiency process for the distance studies systems (DSS) at the expense of using different methods and technologies of knowledge control in training the specialists in higher educational institutions of Ukraine as per Bologna Process regulations. The present teaching methods for creating the resultant DSS have been analysed and new method of knowledge control that allows to adequately estimate the knowledge of those who practices the distance learning (DL) and decrease the control time. The conceptual subsystem for knowledge control (SSKC) and algorithm for tests compiling that allow to provide high authenticity of process in knowledge control when DSS are offered.